2014
DOI: 10.1039/c4tc00572d
|View full text |Cite
|
Sign up to set email alerts
|

Interface control and modification of band alignment and electrical properties of HfTiO/GaAs gate stacks by nitrogen incorporation

Abstract: Effects of nitrogen incorporation on the interface chemical bonding states, optical dielectric function, band alignment, and electrical properties of sputtering-derived HfTiO high-kgate dielectrics on GaAs substrates have been studied by angle resolved X-ray photoemission spectroscopy (ARXPS), spectroscopy ellipsometry (SE), and electrical measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(71 citation statements)
references
References 48 publications
1
70
0
Order By: Relevance
“…(12), plotted in the region of high oxide fields, 1/ E ¼ 0.50e0.66 cm/MV, corresponding to V g ¼ À2.27~À3 V. The experimental ø o values at all temperatures extracted from the slopes of the FeN plots were under 0.20 eV for gate injection. The calculated value of ø o is far away from what we expected, implying that the Fowler-Nordheim tunneling was not a dominant current transport mechanism.…”
Section: Leakage Current-conduction Mechanism Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…(12), plotted in the region of high oxide fields, 1/ E ¼ 0.50e0.66 cm/MV, corresponding to V g ¼ À2.27~À3 V. The experimental ø o values at all temperatures extracted from the slopes of the FeN plots were under 0.20 eV for gate injection. The calculated value of ø o is far away from what we expected, implying that the Fowler-Nordheim tunneling was not a dominant current transport mechanism.…”
Section: Leakage Current-conduction Mechanism Analysismentioning
confidence: 99%
“…In the past decades Hf-based gate dielectric materials, such as, HfTaO, HfTiO, HfZrLaO, HfLaO dielectrics, have been paid more attention due to their thermodynamic stability with silicon channels, preferable band offsets, and reasonably high dielectric constants [8e11]. Especially, the incorporation of titanium element into HfO 2 has attracted considerable attention because TiO 2 has a high dielectric constant (k~80), and a high electron barrier to Si [12,13]. Ye et al have shown that the introduction of TiO 2 into HfO 2 demonstrates the increased crystallization temperature (>700 C) and improved microstructure including interface, surface and amorphous properties [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, the moderate permittivity of Hf-based gate dielectrics will limit its application in future CMOS device scaling with an equivalent oxide thickness (EOT) below 1.0 nm [19][20][21] .Currently, more attention has been paid to study the TiO2 incorporated HfO2, i.e., HfTiO high-k dielectrics, due to its higher k value, remarkable thermal stability, and almost no hysteresis in MOS devices, which has been reported [15,[22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the smaller band offsets at the high-k/IGZO interface and smaller dielectric constant lead to the inferior negative bias and the increased leakage current, which prevents the successful integration of these gate dielectrics into IGZO-based TFTs [15]. Due to its relatively low leakage current, and good thermal stability, HfO 2 has been regarded as one of the most promising gate dielectrics for TFTs [16,17]. However, large frequency dispersion, hysteresis and high leakage current have been also observed [17].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its relatively low leakage current, and good thermal stability, HfO 2 has been regarded as one of the most promising gate dielectrics for TFTs [16,17]. However, large frequency dispersion, hysteresis and high leakage current have been also observed [17]. Inspired by the incorporation of TiO 2 into the dielectric films to improve the dielectric constant, HfTiO were widely applied to prepare gate dielectrics with a high dielectric constant of $25 and a large bandgap of $4.66 eV in Si-based MOS devices [18].…”
Section: Introductionmentioning
confidence: 99%